PRODUCT QUALITY, PERCEIVED VALUE DAN SERVICE QUALITY TERHADAP REPURCHASE INTENTION INDIHOME DENGAN CUSTOMER SATISFACTION SEBAGAI MEDIASI (Studi Pada Mahasiswa Universitas Diponegoro Pengguna Indihome) - Achra, Muhammad Osama; Santosa, Suryono Budi; Hasanatina, Foza Hadyu (Diponegoro Journal of Management, 2024)
ABSTRACT This study aimed to analyze how the quality of the product, how customers feel about the product's value, and the quality of service provided by IndiHome affect whether customers want to buy from them again. It also looked at how happy customers are with IndiHome's services. When customers aren't happy with IndiHome, they might not want to buy their internet service again. The researchers used a method where they collected information from 137 students at Diponegoro University who have used IndiHome's service before. They used a special way to collect this information called a questionnaire and a computer program called AMOS to study the data they collected. The results showed that when the product is good, when customers feel the product is valuable, and when the service is good, customers are happier and more likely to buy from IndiHome again. And when customers are happy with IndiHome, they're more likely to want to buy their service again in the future.